Cross cultural comparison of Automobile Dealerships between UK and India in the light of Market Orientation and Internal Market Orientation. - Chopra, Aashish (2006)
Sales managers are charged with the task of increasing sales whilst at the same time maintaining customer satisfaction. A primary method advocated in the literature to achieve this is market orientation; a construct which places the customer central to the operations of the firm and is designed to collect information to understand the customer and so tailor the product-service offering to best meet their needs. However, additional study into internal market orientation (sometimes known also as employee orientation) implies that sales people will not treat customers in this way if they too do not feel a valued part of the organisation. At present, there is little research into how a firm can use both a market orientation and an internal market orientation to optimize the sales strategy. This study attempts to resolve this gap by developing a conceptual model of their relationship which is then explored through a set of interviews with sales executives in the UK and a comparable set in India to examine for international and cultural differences. It is found that implications are offered as well as avenues for future research. By and large, the main conclusion is that the long-run success for an organization is backed by sales performance which has direct relation with the sales executives.